The Effect of The Alcoholic Extract of Eruca sativa Seeds on Some Blood Biochemical Indicators and Histological Characteristics of Liver in Broiler Chickens Exposed to Lead Acetate Poisoning - sulwan Hana (Basrah Journal of Veterinary Research)
The current study aimed to investigate the impact of adding an alcoholic extract of Eruca sativa seeds and lead acetate to drinking water on some biochemical blood parameters and liver histological changes of broiler chickens. A total of 144 one-day-old Ross 308 broiler chicks, with an initial weight of 40 grams, were randomly distributed into four treatments (each treatment included 36 birds) with three replicates for each (12 birds per replicate). The first treatment was the control group (without any addition); the second treatment added 350 mg of lead acetate per liter of drinking water; the third treatment added 250 mg of the alcoholic extract of Eruca sativa seeds per liter of drinking water, and the fourth treatment added 350 mg of lead acetate and 250 mg of the alcoholic extract of Eruca sativa seeds per liter of drinking water. The results indicated a significant increase (p≤ 0.05) in the total protein and globulin concentration in the third treatment. In contrast, a significant decrease (p≤ 0.05) in the total protein and globulin concentration was observed in the second treatment compared to the other treatments. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were significantly (p≤ 0.05) increased in the second treatment compared to other treatments. A significantly higher (p≤ 0.05) amount of lead concentration was found in the blood serum, breast muscle, liver, and feces of second treatment. On the other hand, these parameters were significantly (p≤ 0.05) decreased in the third treatment compared to the others.